β2-adrenergic receptor agonist counteracts skeletal muscle atrophy and oxidative stress in uremic mice - Higashihara, Takaaki (Sci Rep, 2021)
In patients with chronic kidney disease, skeletal muscle dysfunction is associated with mortality. Uremic sarcopenia is caused by ageing, malnutrition, and chronic inflammation, but the molecular mechanism and potential therapeutics have not been fully elucidated yet. We hypothesize that accumulated uremic toxins might exert a direct deteriorative effect on skeletal muscle and explore the pharmacological treatment in experimental animal and culture cell models. The mice intraperitoneally injected with indoxyl sulfate (IS) after unilateral nephrectomy displayed an elevation of IS concentration in skeletal muscle and a reduction of instantaneous muscle strength, along with the predominant loss of fast-twitch myofibers and intramuscular reactive oxygen species (ROS) generation. The addition of IS in the culture media decreased the size of fully differentiated mouse C2C12 myotubes as well. ROS accumulation and mitochondrial dysfunction were also noted. Next, the effect of the β2-adrenergic receptor (β2-AR) agonist, clenbuterol, was evaluated as a potential treatment for uremic sarcopenia. In mice injected with IS, clenbuterol treatment increased the muscle mass and restored the tissue ROS level but failed to improve muscle weakness. In C2C12 myotubes stimulated with IS, although β2-AR activation also attenuated myotube size reduction and ROS accumulation as did other anti-oxidant reagents, it failed to augment the mitochondrial membrane potential. In conclusion, IS provokes muscular strength loss (uremic dynapenia), ROS generation, and mitochondrial impairment. Although the β2-AR agonist can increase the muscular mass with ROS reduction, development of therapeutic interventions for restoring skeletal muscle function is still awaited.